DESAIN PEMBELAJARAN BAHASA JEPANG MELALUI APLIKASI CHATBOT BERBASIS ARTIFICIAL INTELLIGENCE - tina, ernes; Ellbert Hutabri (LPPM Universitas Putera Batam, 2024)
Being able to speak Japanese in this day and age is very promising social skill in this day and age. This is a result of the large number of Japanese businesses in Indonesia today. However, it can accelerate the career path, on the other hand, it is a communication skill. However, there are so many obstacles in learning it because one of the hardest languages in the world is Japanese that has writing using three different letters, namely hiragana, Katakana, and Kanji. Each elemen of the letter has a different function. Because of this difficulty, it is among the issue that is often experienced by people who want to learn Japanese. Therefore, Japanese Learning Design using Chatbot was created. The chatbot supports an effective and interactive self-learning, which is implemented using the User Centered Design (UCD) method. The outcome of the conducted testing, show that the performance of the application works as it should. Satisfaction evaluation from users shows a positive score, concluding that the application gets very good acceptance from users.